Method for preparing MOFs (Metal-Organic Frameworks) material by utilizing waste polyester chemical fiber fabric

By hydrolyzing the waste PET fabric in an aqueous alkali metal hydroxide solution, terephthalic acid is generated, and reacting with metal salts in a ball mill, the problem of difficulty in recycling color PET textiles is solved, and high-purity MOFs materials are efficiently prepared, avoiding the use of organic solvents and high temperature and high pressure conditions, and reducing costs and reaction time.

CN119505268APending Publication Date: 2025-02-25CHANGCHUN HUANTAI CARBON MICRO TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411652022.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing PET recycling technology is difficult to effectively deal with colored PET textiles, especially due to the presence of dyes and additives, which greatly increases the difficulty of recycling. In addition, the traditional MOF synthesis method has the problem of using a large number of organic solvents, high temperature and high pressure and long reaction times, which limits its industrial application.

Method used

By hydrolyzing the waste PET fabric in an aqueous alkali metal hydroxide solution, terephthalic acid is generated, then the pH is adjusted and the dye is washed and removed, and finally ball milling with the metal salt in a ball mill is carried out to generate a high-purity MOFs material.

Benefits of technology

The efficient recycling of waste PET fabrics is achieved, and high value-added MOFs materials are prepared, which avoids the use of a large number of organic solvents, shortens the reaction time, reduces the cost, and successfully removes the dye, obtains high-quality terephthalic acid, and finally produces MOFs materials with excellent crystallinity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505268A_ABST
    Figure CN119505268A_ABST
Patent Text Reader

Abstract

The invention is applicable to the technical field of degradation of polyester chemical fiber waste fabrics, and provides a method for preparing a metal-organic framework (MOFs) material by using a waste polyester chemical fiber fabric, which comprises the following steps: adding a polyester chemical fiber (PET) waste fabric into an alkali metal hydroxide aqueous solution, hydrolyzing under certain conditions, adjusting the pH value to 3-4, centrifugally collecting precipitate, and drying to obtain the MOFs material. Washing, decolorizing and drying in vacuum to obtain a white solid substance terephthalic acid; and uniformly mixing the obtained pure terephthalic acid with metal salt, and then putting the mixture into a ball mill for ball milling. Washing and collecting the MOFs product obtained after ball milling, and finally performing vacuum drying to obtain the MOFs material. According to the method, the waste colored polyester chemical fiber fabric is decomposed and decolorized, and the MOFs material is massively produced by utilizing mechanochemical ball milling. The method has the advantages of being environmentally friendly, economical, efficient, free of organic solvent and capable of being used for large-scale production, and recycling and high value of the waste clothes are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of degradation of waste polyester chemical fiber fabrics, and in particular relates to a method for preparing MOFs materials by utilizing waste polyester chemical fiber fabrics. Background Art

[0002] Polyester chemical fiber (PET) is a widely used semi-aromatic polyester material, mainly used in the production of textiles and packaging materials. The global annual output is close to 70 million tons, of which more than 60% is used in the textile field. However, the difficulty of degrading polyester chemical fiber makes it an important source of global environmental pollution. Textile-grade PET has higher reactivity in chemical recycling due to its lower intrinsic viscosity (0.4-0.75dL / g), making it particularly suitable for chemical depolymerization. However, complex textile-grade PET, especially colored fabrics containing dyes and other additives, faces technical bottlenecks in recycling and processing.

[0003] Existing PET recycling technologies mainly focus on bottle-grade PET, especially colorless, high-purity waste. However, the presence of dyes and additives in colored PET textiles greatly increases the difficulty of recycling. Dyes not only affect the purity of the recycled products, but may also cause material degradation during the depolymerization process, ultimately leading to performance degradation. Therefore, the effective recycling of PET textiles, especially the removal of impurities such as dyes, has become the focus of technological development.

[0004] Chemical recycling technology is an effective way to degrade PET waste by breaking the ester bonds in PET molecules through hydrolysis to generate the key product terephthalic acid (TPA). As an important chemical raw material, TPA can be further used to synthesize high-value-added materials such as metal-organic frameworks (MOFs).

[0005] However, the traditional MOF synthesis methods (such as solvothermal method) require the use of large amounts of organic solvents (such as N,N-dimethylformamide), high temperatures (150-200°C), high pressures (10×10^5-50×10^5Pa) and long reaction times (12-72h), which limits their industrial applications. In particular, the large-scale synthesis of MOFs materials using waste PET fabrics as precursors still faces challenges in green environmental protection and large-scale production. Summary of the invention

[0006] The purpose of the embodiments of the present invention is to provide a method for preparing MOFs material using waste polyester chemical fiber fabrics, aiming to solve the problems raised in the above background technology.

[0007] The embodiment of the present invention is implemented as follows: a method for preparing MOFs material using waste polyester chemical fiber fabrics, comprising the following steps:

[0008] Step 1, adding the waste PET fabric to an alkali metal hydroxide aqueous solution with a concentration of 0.25 mol / L to 2.5 mol / L, uniformly mixing, heating to 120° C. at a rate of 5° C. / min, and conducting a constant temperature reaction for 120 min. After the reaction is completed, naturally cooling to room temperature to obtain an intermediate product;

[0009] Step 2, adding sulfuric acid solution to the intermediate product obtained in step 1, adjusting the pH value to 3-4, generating a mixed solution, centrifuging the solution, washing the obtained precipitate with ethanol to remove the dye, and vacuum drying to obtain a pure white product terephthalic acid;

[0010] Step 3: Evenly mix the terephthalic acid obtained in step 2 with the metal salt and place them in a ball mill, and perform ball milling reaction at a specific time and rotation speed to allow the metal ions in the metal salt to mechanically react with the terephthalate ions to generate a crude MOFs material, which is then washed and centrifuged and then vacuum dried to obtain a high-purity MOFs material.

[0011] According to a further technical solution, in step 1, the alkali metal hydroxide in the alkali metal hydroxide aqueous solution is LiOH, NaOH or KOH.

[0012] According to a further technical solution, in step 2, the vacuum drying temperature is 60 to 90° C. and the time is 6 to 18 hours.

[0013] According to a further technical solution, in step 3, the metal salt is an aluminum salt, an iron salt, a zirconium salt, a chromium salt, a cobalt salt or a nickel salt.

[0014] According to a further technical solution, in step 3, the molar ratio of terephthalic acid to metal salt is (0.95-1.05):1.

[0015] According to a further technical solution, in step 3, the rotation speed of the ball mill is 250 to 1800 rpm / min, and the time is 30 min to 6 h.

[0016] According to a further technical solution, in step 3, the washing solvent is one or more of N,N-dimethylformamide, water and ethanol; the number of centrifugation is 3 times, the rotation speed is 8000-10000 rpm, and the centrifugation time is 5-15 min.

[0017] According to a further technical solution, in step 3, the vacuum drying temperature is 60°C to 90°C, and the time is 8h to 24h.

[0018] The embodiment of the present invention provides a method for preparing MOFs material using waste polyester chemical fiber fabric, and its beneficial effects are as follows:

[0019] (1) This method achieves efficient recycling of waste PET fabrics and successfully prepares high-value-added MOFs materials; by operating under hydrolysis conditions, PET is degraded into a mixture of terephthalate and a solution containing dyes. In addition, by adjusting the pH value and multiple washing steps, the dyes are successfully removed to obtain high-quality terephthalic acid, which is finally reacted with metal salts in a ball mill to produce MOFs materials with excellent crystallinity;

[0020] (2) By combining the hydrolysis process with mechanochemistry, a green strategy for converting waste PET fabric into MOFs materials was proposed, which provides a new platform for the sustainable large-scale production of MOFs materials. The washing and decolorization steps in the hydrolysis process have no yield loss and are suitable for the preparation of nanoscale MOFs materials.

[0021] (3) This method avoids the use of a large amount of organic solvents and adopts the efficient mixing and reaction mechanism of mechanical ball milling, which not only greatly shortens the reaction time but also effectively reduces the cost. The ball milling process can be controlled by equipment, making the process simple and easy, and the reaction conditions are controllable. It is particularly suitable for large-scale processing of waste polyester chemical fiber PET fabrics.

[0022] (4) This method uses cheap and readily available raw materials, does not require catalysts, is easy to operate, and has low equipment requirements. It can successfully achieve the resource reuse of waste PET fabrics with complex dyeing by combining terephthalic acid obtained in the hydrolysis process and ball milling technology under solvent-free conditions, providing an innovative way for the upgrading and recycling of waste PET fabrics and achieving significant economic and social benefits. In addition, mechanical ball milling, as a green synthesis method of MOFs materials, provides a new direction for the large-scale production of MOFs and shows broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The scanning electron microscope image, physical image and X-ray diffraction spectrum of the Al-MOF material prepared in Example 1;

[0024] Figure 2 The scanning electron microscope image, physical image and X-ray diffraction spectrum of the Fe-MOF material prepared in Example 2;

[0025] Figure 3 The scanning electron microscope image, physical image and X-ray diffraction spectrum of the Zr-MOF material prepared in Example 3;

[0026] Figure 4 The scanning electron microscope image, physical image and X-ray diffraction spectrum of the Cr-MOF material prepared in Example 4;

[0027] Figure 5The scanning electron microscope image, physical image and X-ray diffraction spectrum of the Co-MOF material prepared in Example 5;

[0028] Figure 6 The scanning electron microscope image, physical image and X-ray diffraction spectrum of the Ni-MOF material prepared in Example 6. DETAILED DESCRIPTION

[0029] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0030] The specific implementation of the present invention is described in detail below in conjunction with specific embodiments.

[0031] An embodiment of the present invention provides a method for preparing MOFs material using waste polyester chemical fiber fabric, comprising the following steps:

[0032] Step 1, adding the waste PET fabric to an alkali metal hydroxide aqueous solution with a concentration of 0.25 mol / L to 2.5 mol / L, uniformly mixing, heating to 120° C. at a rate of 5° C. / min, and conducting a constant temperature reaction for 120 min. After the reaction is completed, naturally cooling to room temperature to obtain an intermediate product;

[0033] Step 2, adding sulfuric acid solution to the intermediate product obtained in step 1, adjusting the pH value to 3-4, generating a mixed solution, centrifuging the solution, washing the obtained precipitate with ethanol to remove the dye, and vacuum drying to obtain a pure white product terephthalic acid;

[0034] Step 3: Evenly mix the terephthalic acid obtained in step 2 with the metal salt and place them in a ball mill, and perform ball milling reaction at a specific time and rotation speed to allow the metal ions in the metal salt to mechanically react with the terephthalate ions to generate a crude MOFs material, which is then washed and centrifuged and then vacuum dried to obtain a high-purity MOFs material.

[0035] As a preferred embodiment of the present invention, in step 1, the alkali metal hydroxide in the alkali metal hydroxide aqueous solution is LiOH, NaOH or KOH.

[0036] As a preferred embodiment of the present invention, in step 2, the vacuum drying temperature is 60-90° C. and the time is 6-18 hours.

[0037] As a preferred embodiment of the present invention, in step 3, the metal salt is an aluminum salt, an iron salt, a zirconium salt, a chromium salt, a cobalt salt or a nickel salt.

[0038] As a preferred embodiment of the present invention, in step 3, the molar ratio of terephthalic acid to metal salt is (0.95-1.05):1.

[0039] As a preferred embodiment of the present invention, in step 3, the rotation speed of the ball mill is 550-1800 rpm / min, and the time is 30 min-6 h.

[0040] As a preferred embodiment of the present invention, in step 3, the washing solvent is one or more of N,N-dimethylformamide, water and ethanol; the number of centrifugation is 3 times, the rotation speed is 8000-10000 rpm, and the centrifugation time is 5-15 min.

[0041] As a preferred embodiment of the present invention, in step 3, the vacuum drying temperature is 60° C. to 90° C., and the time is 8 h to 24 h.

[0042] Several specific examples are provided below to verify the effectiveness of this method.

[0043] Embodiment 1:

[0044] Step 1, adding 2.0 g of waste PET fabric to 200 mL of 2 mol / L NaOH aqueous solution, mixing evenly, heating from room temperature to 120° C. at a heating rate of 5° C. / min, performing a hydrolysis reaction at a constant temperature for 120 min, and naturally cooling to room temperature to obtain an intermediate product, i.e., a mixed aqueous solution of impurities such as disodium terephthalate, ethylene glycol, and dyes;

[0045] Step 2, adding sulfuric acid solution to the intermediate product obtained in step 1 to adjust the pH value to 3-4 to obtain a mixed solution, centrifuging, collecting the precipitate, washing with ethanol three times to remove the colored dye, and vacuum drying at 80° C. for 12 hours to obtain terephthalic acid (TPA) as a white solid;

[0046] Step 3: Evenly mix 10 mmol (1.66 g) of terephthalic acid obtained in step 2 and 10 mmol (3.75 g) of aluminum nitrate nonahydrate and place them in a ball mill. Mill them at a speed of 600 rpm / min for 4 hours to obtain a mixed product containing a crude Al-MOF product. Disperse the product in ethanol and filter to remove residual raw materials. Wash the precipitated material with ethanol three times, collect the precipitate by centrifugation at 8000 r / min, and vacuum dry it at 80°C for 12 hours to obtain a MOF material, i.e., an Al-MOF material.

[0047] Figure 1a and b are scanning electron microscope images of Al-MOF materials, c is a physical image of Al-MOF materials, and d is an X-ray diffraction spectrum of Al-MOF materials. From the scanning electron microscope image, it can be seen that the morphology of Al-MOF materials is irregular and has a rod-like structure. From the X-ray powder diffraction spectrum, it can be seen that Al-MOF materials have significant characteristic diffraction peaks, indicating the successful synthesis of Al-MOF materials.

[0048] Embodiment 2:

[0049] Step 1, adding 2.0 g of PET waste fabric to 200 mL of a 2.5 mol / L KOH aqueous solution, mixing evenly, heating from room temperature to 120° C. at a heating rate of 5° C. / min, performing a hydrolysis reaction at a constant temperature for 120 min, and naturally cooling to room temperature to obtain an intermediate product, i.e., an aqueous solution of impurities such as dipotassium terephthalate, ethylene glycol, and dyes;

[0050] Step 2, adding sulfuric acid solution to the intermediate product obtained in step 1 to adjust the pH value to 4 to obtain a mixed solution, centrifuging, collecting the precipitate, washing and decolorizing with ethanol 4 times, and vacuum drying at 80° C. for 12 hours to obtain terephthalic acid as a white solid;

[0051] Step 3: Mix 10 mmol (1.66 g) of terephthalic acid obtained in step 2 and 10 mmol (2.70 g) of ferric chloride hexahydrate evenly and place them in a ball mill. Mill them at a speed of 550 rpm / min for 4 hours to obtain a mixed product containing a crude Fe-MOF product. Disperse the product in ethanol and filter to remove residual raw materials. Wash the precipitated material with ethanol three times, collect the precipitate by centrifugation at 9000 r / min, and vacuum dry it at 80°C for 12 hours to obtain a MOF material, namely, a Fe-MOF material.

[0052] Figure 2 Figures a and b are scanning electron microscope images of Fe-MOF materials, c is a physical image of Fe-MOF materials, and d is an X-ray diffraction spectrum of Fe-MOF materials. From the scanning electron microscope image, it can be seen that the morphology of Fe-MOF materials is irregular and has a bulk structure. From the X-ray powder diffraction spectrum, it can be seen that Fe-MOF materials have significant characteristic diffraction peaks, indicating the successful synthesis of Fe-MOF materials.

[0053] Embodiment 3:

[0054] Step 1, adding 2.0 g of PET waste fabric to 200 mL of 1.5 mol / L NaOH aqueous solution, mixing evenly, heating from room temperature to 120° C. at a heating rate of 5° C. / min, performing a hydrolysis reaction at a constant temperature for 120 min, and naturally cooling to room temperature to obtain an intermediate product, i.e., an aqueous solution of impurities such as dilithium terephthalate, ethylene glycol, and dyes;

[0055] Step 2, adding hydrochloric acid solution to the intermediate product obtained in step 1 to adjust the pH value to 4 to obtain a mixed solution, centrifuging, collecting the precipitate, washing and decolorizing with ethanol 4 times, and vacuum drying at 80° C. for 12 hours to obtain terephthalic acid as a white solid;

[0056] Step 3: Mix 10 mmol (1.66 g) of terephthalic acid obtained in step 2 and 10 mmol (3.22 g) of zirconium oxychloride octahydrate evenly in a ball mill, and mill at a speed of 650 rpm / min for 30 min to obtain a mixed product containing a crude Zr-MOF product. The product is dispersed in ethanol and filtered to remove residual raw materials. The precipitated material is washed three times with deionized water and ethanol, and the precipitate is collected by centrifugation at 9000 r / min. After vacuum drying at 80°C for 18 h, a MOF material is obtained, namely, a Zr-MOF material.

[0057] Figure 3 a and b in the figure are scanning electron microscope images of Zr-MOF materials, c is a physical image of Zr-MOF materials, and d is an X-ray diffraction spectrum of Zr-MOF materials. From the scanning electron microscope image, it can be seen that the morphology of Zr-MOF materials is irregular and is a block material. From the X-ray powder diffraction spectrum, it can be seen that Zr-MOF materials have significant characteristic diffraction peaks, indicating the successful synthesis of Zr-MOF materials.

[0058] Embodiment 4:

[0059] Step 1, adding 2.0 g of PET waste fabric to 100 mL of a 2 mol / L NaOH aqueous solution, mixing evenly, heating from room temperature to 120° C. at a heating rate of 5° C. / min, performing a hydrolysis reaction at a constant temperature for 120 min, and naturally cooling to room temperature to obtain an intermediate product, namely, disodium terephthalate and an ethylene glycol aqueous solution;

[0060] Step 2, adding sulfuric acid solution to the intermediate product obtained in step 1 to adjust the pH value to 4 to obtain a mixed solution, centrifuging, collecting the precipitate, washing and decolorizing with ethanol 4 times, and vacuum drying at 80° C. for 12 hours to obtain terephthalic acid as a white solid;

[0061] Step 3: Mix 10 mmol (1.66 g) of terephthalic acid obtained in step 2 and 10 mmol (2.66 g) of chromium trichloride hexahydrate evenly and place them in a ball mill. Mill them at a speed of 1800 rpm / min for 1 hour to obtain a mixed product containing a crude Cr-MOF product. Disperse the product in ethanol and filter to remove residual raw materials. Wash the precipitate with ethanol 3 times, collect the precipitate by centrifugation at 10000 r / min, and vacuum dry at 90°C for 24 hours to obtain a metal-organic framework material, i.e., Cr-MOF material.

[0062] Figure 4 Figures a and b are scanning electron microscope images of Cr-MOF materials, c is a physical image of Cr-MOF materials, and d is an X-ray diffraction spectrum of Cr-MOF materials. From the scanning electron microscope image, it can be seen that the morphology of Cr-MOF materials is irregular, with a block structure and a size greater than 1 μm. From the X-ray powder diffraction spectrum, it can be seen that Cr-MOF materials have significant characteristic diffraction peaks, indicating the successful synthesis of Cr-MOF materials.

[0063] Embodiment 5:

[0064] Step 1, adding 2.5g of PET waste fabric to 100mL of 0.5mol / L NaOH aqueous solution, mixing evenly, heating from room temperature to 120°C at a heating rate of 5°C / min, performing a hydrolysis reaction at a constant temperature for 120min, and naturally cooling to room temperature to obtain an intermediate product, namely disodium terephthalate and an ethylene glycol aqueous solution;

[0065] Step 2, adding sulfuric acid solution to the intermediate product obtained in step 1 to adjust the pH value to 3 to obtain a mixed solution, centrifuging, collecting the precipitate, washing and decolorizing with ethanol 3 times, and vacuum drying at 80° C. for 12 hours to obtain terephthalic acid as a white solid;

[0066] Step 3: Mix 12 mmol (2.05 g) of terephthalic acid obtained in step 2 and 12 mmol (3.50 g) of cobalt nitrate hexahydrate evenly and place them in a ball mill. Mill them at a speed of 700 rpm / min for 4 hours to obtain a mixed product containing a crude Co-MOF product. Disperse the product in ethanol and filter to remove residual raw materials. Wash the precipitated material with ethanol three times, collect the precipitate by centrifugation at 10000 r / min, and vacuum dry it at 100°C for 12 hours to obtain a MOF material, namely a Co-MOF material.

[0067] Figure 5a and b are scanning electron microscope images of Co-MOF materials, c is a physical image of Co-MOF materials, and d is an X-ray diffraction spectrum of Co-MOF materials. From the scanning electron microscope image, it can be seen that the morphology of Co-MOF materials is irregular and has a block-like structure. From the X-ray powder diffraction spectrum, it can be seen that Co-MOF materials have significant characteristic diffraction peaks, indicating the successful synthesis of Co-MOF materials.

[0068] Embodiment 6:

[0069] Step 1, adding 2.5 g of PET waste fabric to 100 mL of a 2 mol / L NaOH aqueous solution, mixing evenly, heating from room temperature to 120° C. at a heating rate of 5° C. / min, performing a hydrolysis reaction at a constant temperature for 120 min, and naturally cooling to room temperature to obtain an intermediate product, namely, disodium terephthalate and an ethylene glycol aqueous solution;

[0070] Step 2, adding sulfuric acid solution to the intermediate product obtained in step 1 to adjust the pH value to 3 to obtain a mixed solution, centrifuging, collecting the precipitate, washing and decolorizing with ethanol 3 times, and vacuum drying at 80° C. for 12 hours to obtain terephthalic acid as a white solid;

[0071] Step 3: Mix 12 mmol (2.05 g) of terephthalic acid obtained in step 2 and 12 mmol (3.4 g) of nickel nitrate hexahydrate evenly and place them in a ball mill. Mill them at a speed of 600 rpm / min for 4 hours to obtain a mixed product containing a crude Ni-MOF product. Disperse the product in ethanol and filter to remove residual raw materials. Wash the precipitated material with ethanol three times, collect the precipitate by centrifugation at 8000 r / min, and vacuum dry it at 90°C for 8 hours to obtain a MOF material, namely a Ni-MOF material.

[0072] Figure 6 Figures a and b are scanning electron microscope images of Ni-MOF materials, c is a physical image of Ni-MOF materials, and d is an X-ray diffraction spectrum of Ni-MOF materials. From the scanning electron microscope image, it can be seen that the morphology of Ni-MOF materials is irregular and has a block structure. From the X-ray powder diffraction spectrum, it can be seen that Ni-MOF materials have significant characteristic diffraction peaks, indicating the successful synthesis of Ni-MOF materials.

[0073] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing MOFs material using waste polyester chemical fiber fabric, characterized in that: The following steps are involved: Step 1, adding the waste PET fabric to an alkali metal hydroxide aqueous solution with a concentration of 0.25 mol / L to 2.5 mol / L, uniformly mixing, heating to 120° C. at a rate of 5° C. / min, and conducting a constant temperature reaction for 120 min. After the reaction is completed, naturally cooling to room temperature to obtain an intermediate product; Step 2, adding sulfuric acid solution to the intermediate product obtained in step 1, adjusting the pH value to 3-4, generating a mixed solution, centrifuging the solution, washing the obtained precipitate with ethanol to remove the dye, and vacuum drying to obtain a pure white product terephthalic acid; Step 3: Evenly mix the terephthalic acid obtained in step 2 with the metal salt and place them in a ball mill, and perform ball milling reaction at a specific time and rotation speed to allow the metal ions in the metal salt to mechanically react with the terephthalate ions to generate a crude MOFs material, which is then washed and centrifuged and then vacuum dried to obtain a high-purity MOFs material.

2. The method for preparing MOFs material using waste polyester chemical fiber fabric according to claim 1, characterized in that: In step 1, the alkali metal hydroxide in the alkali metal hydroxide aqueous solution is LiOH, NaOH or KOH.

3. The method for preparing MOFs material using waste polyester chemical fiber fabric according to claim 1, characterized in that: In step 2, the vacuum drying temperature is 60 to 90° C. and the time is 6 to 18 hours.

4. The method for preparing MOFs material using waste polyester chemical fiber fabric according to claim 2, characterized in that: In step 3, the metal salt is an aluminum salt, an iron salt, a zirconium salt, a chromium salt, a cobalt salt or a nickel salt.

5. The method for preparing MOFs material using waste polyester chemical fiber fabric according to claim 4, characterized in that: In step 3, the molar ratio of terephthalic acid to metal salt is (0.95-1.05):

1.

6. The method for preparing MOFs material using waste polyester chemical fiber fabric according to claim 1, characterized in that: In step 3, the rotation speed of the ball mill is 250 to 1800 rpm / min, and the time is 30 min to 6 h.

7. The method for preparing MOFs material using waste polyester chemical fiber fabric according to claim 5, characterized in that: In step 3, the washing solvent is one or more of N,N-dimethylformamide, water and ethanol; the number of centrifugation is 3 times, the rotation speed is 8000-10000 rpm, and the centrifugation time is 5-15 min.

8. The method for preparing MOFs material using waste polyester chemical fiber fabric according to claim 6, characterized in that: In step 3, the vacuum drying temperature is 60° C. to 90° C., and the time is 8 h to 24 h.